FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP KUALITAS LAPORAN KEUANGAN PEMDA KOTA JAMBI TAHUN 2021 - Mellya Embun Baining; Titin Agustin Nengsih; Suci Ramadhani (AT-TIJARAH: Jurnal Penelitian Keuangan dan Perbankan Syariah, 2021)
Financial reports must be of high quality. Good financial reporting from local governments gets an unconditional opinion (WTP) from the Supreme Audit Agency (BPK). The purpose of this study is to see the application of Government Accounting Standards, Utilization of Information Technology, Effectiveness of Human Resources,. and the Internal Control System on the quality of the Jambi City Government's financial reporting. The population in this study is Local Government Organizations (OPD) in Jambi City. The use of saturated sampling technique in this study consisted of 40 respondents. This research was conducted using several multiple linear regression equations. Based on the results of the test analysis, it is known that the Government Accounting Standards, the use of Information Technology, and the competence of Human Resources have no effect on the quality of financial reports. In addition, the Internal Control System variable shows a significant effect on the quality of financial reporting. Based on the F test, for SAP, the use of IT, HR competencies and SPI affect the quality of Jambi city financial reporting in 2021.